A case of retrobulbar optic neuritis caused by duloxetine. (2nd July 2016) - Bicer, Tolga; Kosker, Mustafa; Celikay, Osman; Gurdal, Canan
Abstract: Psychotropic medications may cause many ocular adverse effects including toxic optic neuropathy. We present a unique case of a 44-year-old woman using duloxetine who presented with unilateral visual loss due to retrobulbar neuritis. Physicians and patients should be alerted to this potential side effect. To the best of our knowledge, this is the first case of developing retrobulbar neuritis related to duloxetine usage.